Protective Role of Urtica dioica Extract on MDA Levels, Epididymal p53 mRNA, and Sperm Profile in Obese Sprague–Dawley Rats - Harni Sutiani; Kabir Ardiansyah tangkari; Jurnalis Gempaning Tyas; Zaenudin; Dicky Mohammad Rizal; Jajar Setiawan (Majalah Biomorfologi, 2026)
Background: Obesity, resulting from an imbalance between energy intake and expenditure, leads to excessive fat accumulation and is associated with metabolic disorders and male infertility. Increased oxidative stress in obesity contributes to impaired spermatogenesis, altered sperm quality, and disruption of reproductive function. Urtica dioica contains bioactive compounds with antioxidant, anti-inflammatory, and anti-apoptotic properties. Objective: To evaluate the effect of Urtica dioica extract on malondialdehyde (MDA) levels, epididymal p53 mRNA expression, and sperm quality in obese male rats. Materials and Methods: The authors conducted an experimental study in 25 male Sprague–Dawley rats, divided into five groups (n = 5): non-obese control, obese control, and three treatment groups (125, 250, and 500 mg/kg BW). Obesity was induced using a high-fat and fructose diet for 6 weeks, followed by 4 weeks of treatment. We measured MDA levels using the TBARs, p53 mRNA expression by PCR, and sperm parameters according to WHO standards. Data were analyzed using ANOVA or Kruskal–Wallis tests (p < 0.05). Results: Obese groups demonstrated higher body weight and Lee index of > 300 (p < 0.001). The administration of Urtica dioica extract at 500 mg/kg BW resulted in a significant decrease in MDA levels and an increase in p53 mRNA expression compared to the obese control (p < 0.05), which demonstrated higher sperm concentration, motility, and viability, along with lower morphological abnormalities than those in obese controls (p < 0.05). Conclusion: Urtica dioica extract at 500 mg/kg BW exhibits protective effects against oxidative stress and improves reproductive parameters in obese male rats.